NILAI TAMBAH DAN STRATEGI PENGEMBANGAN PRODUK PADA AGRONDUSTRI KOPI BUBUK CAP GUNUNG DI KABUPATEN WAY KANAN - Ragil Crysanti Wiryaningsih; Dwi Haryono; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze and calculate the added value of Cap Gunung coffee powder agro-industry, and arrange the development strategy of Cap Gunung coffee powder agro-industry products. The method that used in this research is a case study. Therefore, the analytical method that used is the Hayami Method and Strength, Weakness, Opportunity, Threats (SWOT) Analysis. Based on the calculation of the value added is Rp13,386/kg with a value added ratio is 32.81 percent. Furthermore, results of the SWOT analysis show that the values of internal and external factors are 78.8 and 64.9. This value indicate that the Cap Gunung coffee powder agro-industry in quadrant I, or in the Strength-Opportunity (SO) strategy. The priority strategy that can be implemented is to expand the marketing area, increase production output, and develop businesses by utilizing their strengths.Keywords: added value, development strategy, hayami method, SWOT analysis